Drug design and synthesis of cox-2 selective inhibitors as potential NSAIDs / Abeer Abdulhadi Abdulqader - Abeer Abdulhadi , Abdulqader (2016)
Cyclooxygenase (COX) is a key enzyme in the biosynthetic pathway leading to the formation of prostaglandins, which are mediators of inflammation. It exists mainly in two isoforms, COX-1 and COX-2. The conventional nonsteroidal anti-inflammatory drugs (NSAIDs) have gastrointestinal side effects because they inhibit both isoforms. Recent studies show that the inhibition of cyclooxygenase-2 can delay or prevent certain forms of cancer. Agents that inhibit COX-2 while sparing COX-1 represent a new attractive therapeutic development and offer a new perspective for a further use of COX-2 inhibitors. The present study extends the evaluation of COX activity to a series of 1,3,4-oxadiazoline derivatives (3a-h) following a rational approach consisting molecular modeling, synthesis, and biological tests. Based on data obtained from molecular modeling, a set of compounds with better profiles of affinity have been synthesized and tested for COX-2 inhibition in vitro. All compounds (3a-h) showed reasonable inhibitory profiles against COX-2 but not COX-1, indicating that they are selective inhibitors for COX-2. Moreover, the study showed that compound 3h to be the best selective COX-2 inhibitor among the tested compounds with selectivity index in the range of 175, while compounds 3a, 3b, 3c and 3d showed moderate selectivity. Our results suggested that these novel compounds may have potential as structural templates for the design and subsequent development of the new selective COX-2 inhibitor drugs. The unique chemical structure of the compounds and their effect on COX enzyme binding and activity as well as their potency and selectivity, may prove useful in treating pain and inflammation.